JEWISH CULTURE IN LA CARTE ET LE TERRITOIRE FOSTERING CULTURAL AWARENESS TROUGH TRAVEL WRITING - Safrina Arifiani Felayati; Chendy Arieshanty Paramytha Sulistyo; Riefki Fajar Ganda Wiguna (CLLiENT (Culture, Literature, Linguistics, and English Teaching), 2022)
Travel writing is a genre of writing in which the author describes places they have visited and their experiences while traveling. It can be concluded that there must be many cultures described in travel writing. Cultural diversity is reflected in the wide variety of values, beliefs, attitudes and rules that define regional, ethnic, religious and other culture groups. This research explains how the author describes the diversity of cultures, with the main character as a Jew, we will see a lot of how Jewish culture is depicted in this novel. Through travel writing, we will learn a lot about cultural diversity. By reading a lot of travel writing, we will further increase our knowledge about cultural diversity, so that it can increase our cultural awareness. Whereas cultural diversity represents variation in culture, cultural awareness reflects the degree of awareness the learners may have towards different cultures in order to take the appropriate action to avoid any kind of cultural conflict if it happens in their educational context. La carte et le Territoire by Michel Houellebecq tells about a Jews travel in France and around Europe. This research uses a historical method, comparison, logical interference, deduction induction, and syllogism.